Development of new non-dairy beverages from Mediterranean fruit juices fermented with water kefir microorganisms. (April 2016) - Randazzo, Walter; Corona, Onofrio; Guarcello, Rosa; Francesca, Nicola; Germanà, Maria Antonietta; Erten, Hüseyin; Moschetti, Giancarlo; Settanni, Luca
Abstract: The aim of this work was to explore the use of several Mediterranean fruit juices as fermentable substrates to develop new non-dairy fermented beverages. Microbiological, chemical and sensory features of kefir-like beverages obtained after the fermentation of juices extracted from fruits cultivated in Sicily (southern Italy) with water kefir microorganisms were investigated. Results indicated that both lactic acid bacteria and yeasts were able to develop in the fruit juices tested, but the highest levels were registered with prickly pear fruit juice. All fruit juices underwent a lactic fermentation, since a lactic acid content was detected in the resulting kefir-like beverages. Except kiwifruit and quince based kefirs, total titratable acidity increased for the other experimental products. A general decrease of the soluble solid content and an increase of the number of volatile organic compounds (VOCs) was also observed after fermentation. As expected, the fermentation increased the concentration of alcohols. The main fermentation in KLBs resulted to be yeast-based. Kiwifruit and pomegranate juices possessed a high antioxidant activity. Esters compounds were present at higher amount after the fermentation, especially in grape, pomegranate and quince. Aldehydes showed an opposite trend. Changes in colour attributes were registered as noticeable at human perception scale. The overall quality evaluation indicated that, among the Mediterranean fruit juices tested, apple and grape beverages were the products mostly appreciated by the tasters. Therefore, these findings support the possibility to develop fruit-based kefir-like beverages with high added value and functional properties. Highlights: Six Mediterranean fruit juices allowed the development of water kefir microorganisms. The highest microbial counts were registered during transformation of prickly pear. All fruit juices underwent lactic and alcoholic fermentation. Apple and grape kefir-like beverages were mostly appreciated by the judges.